KONTEKS GLASS CEILING : KAPABILITAS, REKRUITMEN, DAN REPRESENTASI WANITA (MEN AND WOMEN : WHAT’S THE DIFFERENCES?) - Qodriah, Sari Laelatul; Kusuma, Irena Tiara (VALUE, 2018)
This study aim to obtain empirical evidence whether or not the influence of capability and recruitment to woman representation. This research using correlational quantitative method and data processing assisted with SPSS 20. Population of this reasearch are 6 political parties that exist in Cirebon Regency. The results of this study indicated that only varaible capability has a positive and significant influence on the woman representation and has a correlation between variables in the medium category. While the recruitment variable  has  a  correlational  between  the  variables  in  the  low  category  and  it  is  not significant. Keyword : capability, recruitment, woman representation, political party